1998
DOI: 10.1093/oxfordjournals.jmicro.a023604
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic observations and X-ray microanalysis of a multinucleated giant cell

Abstract: Giant cells and macrophages play important roles in defence and in reparative functions of the body. This paper describes a giant cell and macrophage present in an inflammatory mass in the temporal bone. X-ray microanalysis performed at the ultrastructural level revealed the presence of a very high iron content in the electron dense precipitates observed in both types of cells. The high iron content is probably due to phagocytosed haemosiderin, a breakdown product of free haemoglobin since there was evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Immunoelectron Microscopy-The rats were perfused in 0.5% glutaraldehyde and 4% paraformaldehyde before processing for electron microscopy (EM) as described previously (32). Briefly, post-osmicated samples were dehydrated in an ascending series of ethanol and embedded in araldite.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoelectron Microscopy-The rats were perfused in 0.5% glutaraldehyde and 4% paraformaldehyde before processing for electron microscopy (EM) as described previously (32). Briefly, post-osmicated samples were dehydrated in an ascending series of ethanol and embedded in araldite.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue from a confirmed undifferentiated NPC (by light microscopy) was fixed in 3% glutaraldehyde and 2% paraformaldehyde before osmication in 2% osmium tetroxide as previously described (Bay et al, 1998). Post-osmicated samples were dehydrated in an ascending series of ethanol and embedded in epoxy resin.…”
Section: Transmission Electron Microscopy and Immunoelectron Microscopymentioning
confidence: 99%
“…Several studies have reported that inflammatory multinucleated giant cells (3) and macrophages, especially those in the lymph nodes, phagocytose iron nanoparticles (4 -7), but nothing is known about the fate of extracellular particles.…”
mentioning
confidence: 99%